One in a Million: A Case Report of Stiff Person Syndrome - Ruchi Yadav; Neeraj Abrol; Sima Terebelo (Case Reports in Rheumatology)
Stiff person syndrome (SPS) is a rare autoimmune disease caused by lack of inhibition to excitatory neurotransmitters in the central nervous system (CNS) leading to inappropriate motor unit firing. The pathophysiology is incompletely understood; however, high titers of antiglutamic acid decarboxylase antibody (anti-GAD Ab) are strongly associated with this disease. We present a 50-year-old woman with a history of ongoing gait and balance issues for 5 years with multiple negative workups. She recently had an acute exacerbation which left her bedbound, unable to move her legs or turn from side to side. After a negative workup at an outside hospital, the patient was discharged to a subacute rehabilitation facility. She then presented to our institution due to worsening of her condition and was ultimately diagnosed with SPS which was successfully treated. We review the case presentation and treatment options in the context of a severe disabling disease presentation.